2020
DOI: 10.1371/journal.pone.0236573
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of physical activity and sedentary behavior among South Asian adults: A systematic review

Abstract: Background South Asians are one of the fastest growing ethnic groups in western countries with a high incidence of chronic diseases like metabolic syndrome and cardiovascular disease occurring at younger ages and lower body weight compared with white Europeans. Physically active lifestyle and reduced sedentary time are modifiable risk factors that can decrease burden of chronic diseases. Population-level surveys based on self-report show South Asians engage in low levels of physical activity. Because of known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 72 publications
(112 reference statements)
0
12
2
1
Order By: Relevance
“…The review's main findings are that South Asian adults engage in a mean daily sedentary time of approximately 7 h (424 ± 8 min), although sedentary time varies widely between self-reported and objective measures. The daily sedentary time of South Asians in the present review is lower than the 482 to 587 min/day reported by Mahmood et al [26]. This discrepancy may be due to Mahmood et al [26] reporting total mean sedentary time based on accelerometer data only (i.e., ActiGraph and ActiHeart), whereas the current review reports total sedentary time in South Asians based on both objective and subjective measurement methods.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The review's main findings are that South Asian adults engage in a mean daily sedentary time of approximately 7 h (424 ± 8 min), although sedentary time varies widely between self-reported and objective measures. The daily sedentary time of South Asians in the present review is lower than the 482 to 587 min/day reported by Mahmood et al [26]. This discrepancy may be due to Mahmood et al [26] reporting total mean sedentary time based on accelerometer data only (i.e., ActiGraph and ActiHeart), whereas the current review reports total sedentary time in South Asians based on both objective and subjective measurement methods.…”
Section: Discussioncontrasting
confidence: 85%
“…The daily sedentary time of South Asians in the present review is lower than the 482 to 587 min/day reported by Mahmood et al [26]. This discrepancy may be due to Mahmood et al [26] reporting total mean sedentary time based on accelerometer data only (i.e., ActiGraph and ActiHeart), whereas the current review reports total sedentary time in South Asians based on both objective and subjective measurement methods. However, based on the weighted sedentary time of the studies that used objective methods in the present review, daily sedentary time was 527 min/day, which is similar to the range reported in the systematic review by Mahmood et al [26].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Accelerometers are particularly useful to measure PA and sedentary time in diverse ethnic groups where English proficiency may be limited and where conceptualization of PA and sedentary time may be heavily influenced by cultural factors [ 11 , 19 ]. While there has been a rapid increase in the use of accelerometers in the past decade, our recent systematic review concluded that up until March 2019, just 14 studies (with only three of those based in North America) used this technology to measure PA levels and/or sedentary time in South Asians [ 20 ].…”
Section: Introductionmentioning
confidence: 99%